Genetic association analysis with R: latest developments - Zhao, Jing Hua (Henry Stewart Talks, 2026)
Linux and R, Language elements, Genome Wide Association Study (GWAS) packages, AI related packages, biomaRT, GUI and shiny, Package development and distribution via GitHub, Web distribution